Moving Children through Private International Law: Institutions and the Enactment of Ethics. - van Wichelen, Sonja (Law & Society Review, 2019)
This article examines how the Hague Convention on the Protection of Children and Co‐operation in Respect of Intercountry Adoption (Hague Adoption Convention) plays a central role in justifying the institution of legal adoption. The Hague Adoption Convention has often been regarded as a response to the challenges that the "global situation" brings to adoption practice. Based on private international law, the agreement contains protocols and norms to ensure the protection of the child in intercountry adoption. In the article, I propose that the Hague Convention can be understood as a "transparency device"; a complex assemblage working in pursuit of global "good governance." The device, however, also operates as justification within the institutional domain, allowing adoption agencies to make distinctions between legitimate and illegitimate adoptions. Idemonstrate how the logic of transparency disguises as much as it promises to reveal. While the doctrine's aim is to validate adoptability and combat trafficking, it also helps to mainstream Euro‐American adoption knowledge to other parts of the world.